The Teacher's Body: Embodiment, Authority, and Identity in the Academy (Teaching theology and religion, 2006)
Books reviewed: Freedman, Diane P. and Holmes, Martha Stoddard, eds., The Teacher's Body: Embodiment, Authority, and Identity in the Academy Reviewed by Rosemary P. Carbine College of the Holy Cross